The moderating roles of audit committee tenure and audit partner tenure on the relationships between audit committee characteristics and earnings management - Al-Hameedy, Mohammed Degan Abdul Amir (2022)
The objective of this study was to examine the relationship between audit committee characteristics and earnings management. Furthermore, this study examined the moderating effect of the independent audit committee tenure and the audit partner tenure on the relationship between audit committee characteristics and earnings management. This study used a sample of 594 companies listed on the Main Market of Bursa Malaysia over the period of 2014 to 2016. The performance-matched model proposed by Kothari was used to measure earnings management. In addition, this study employed the Feasible Generalized Least Square (FGLS) regression as it provides reliable estimates in the presence of the heteroscedasticity problem. This study revealed that audit committee accounting expertise, chair accounting expertise, chair age and audit committee independence reduce earnings management practice. However, the chair workload increases the level of earnings management. Meanwhile, this study found that audit committee ethnicity and meetings have no effect on earnings management. The results also showed that independent audit committee tenure moderates the relationship between chair accounting expertise, chair workload, and audit committee independence with earnings management. However, independent audit committee tenure finds no evidence to moderate the relationship between audit committee accounting expertise, chair age, ethnicity and meetings with earnings management. Furthermore, the audit partner tenure moderates the relationship between chair accounting expertise, chair workload, chair age and ethnicity with earnings management. However, the study found no evidence to support audit partner tenure to moderate the relationship between accounting expertise, independence and meetings with earnings management. The results of this study have implications for investors, regulators and market participants. This study alerts policy-makers and regulators such as Bursa Malaysia and the Securities Commission regarding the important characteristics of the audit committee and the relevance of the tenure of independent audit committee members and audit partners in Malaysian companies.